MOLECULAR DIVERSITY OF nrDNA ITS REGION AFFECTED HETEROSIS IN SUNFLOWER (Helianthus annuus) - & et al, Kanoosh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A study was conducted to specify mutations of the internal transcribed spacer (ITS) in the nucleotides of nuclear ribosomal DNA (nrDNA) and their molecular relationship with heterosis exhibited by the six A- lines and three R-testers of sunflower. The trail was conducted at the fields of the College of Agriculture, University of Anbar, Abu Ghraib during two seasons (spring and fall 2016). Parental lines were crossed according to lineΧtester crossing scheme to produce 18 single hybrids, genotypes were sown to assess their phenotypic performance in the fall season. Results of the molecular analysis of ITS sequencing showed that the rearrangement of single nucleotides had accumulated in a higher rate in the F1 hybrids compared with their ancestor inbreds. The total number of mutations was 268, and deletion mutations accounted for the largest proportion with 209 mutation (71 in lines and 138 in hybrids). In contrast, the transition mutations were 25 all occurred in the hybrids, however the number of transversions recorded 17only. Based on DNA sequence of the nrDNA ITS region the total genotypes were separated into two main groups in cluster analysis following the nearest neighbor method. There was a significant convergence between R2 and both A4ΧR2 and A6ΧR3 hybrids scoring higher values of similarity in context ITS sequence. To be specific, the hybrid A2ΧR3 exhibited the best desirable heterosis for days to 75% flowering and leaf area, while hybrid A5ΧR3 had the highest heterosis for head traits, height and area.